Strategies To Increase Production And Business Management In Sago Hot (Cooking) Refill Water Businesses For Small Industrial Businesses In Kenagarian Lareh Sago Halaban Payakumbuh: Strategi Untuk Meningkatkan Produksi Dan Manajemen Usaha Pada Usaha Air Isi Ulang Panas (Masak) Sago Pada Pelaku Usaha Industri Kecil Di Kenagarian Lareh Sago Halaban Payakumbuh - Syahril; Yesi Elsandra; Dedi Julianto; Aulia Fransiska; Desi Amalia Putri (Journal of Community Service and Application of Science, 2023)
MSMEs are small and medium enterprises managed by one or more people with simple business management with various kinds of problems. Like in this Sago refill boiled water business where the management of the business is not in accordance with the prevailing theory, such as the leadership is not yet clear because everyone in the business is the leader, therefore this business is not well managed, besides that, there is also a production problem, there is no specified target. per day, while the demand is high, sometimes the demand cannot be fulfilled by the business manager. Furthermore, the problem of product marketing is still local and has not been fulfilled by business managers. Based on this, the author is interested in using this title as a community service activity while this business has the potential to be developed in the Sago Halaban Payakumbuh area. In this community service, the author uses counseling and guidance methods which include lectures and guidance 245%, role play 25%, active learning 15% and participation 15%.